City character and standardisation – A historical perspective – The case of Delft - de Vries, Henk J. (Journal of Standardisation, 2025)
This paper explores the relation between a city’s character and standardisation activities in that city, taking the case of the Dutch city of Delft. In Delft’s 2000 years of history, and in the current situation, many cases of standards development and use can be found. The analysis shows that these show a huge variety. Several cases go beyond ‘normal,’ and had or have substantial impact. This strong standardisation profile is in line with the city’s character expressed in its branding. However, causal relationships cannot be found. The paper seeks for alternative explanations for the correlations. Future research may deepen this study and replicate it in other cities.